IBM DI KELURAHAN PATEMON GUNUNGPATI SEMARANG DALAM MENGEMBANGKAN KEWIRAUSAHAAN BIDANG BUSANA - Sawitri, Sicilia; Prawetyaningtyas, Wulansari; Rachmawati, Rina (Universitas Negeri Semarang, 2015)
The problem which want to overcome in this activity was: how to design marketing and packaging techniques in order to improve patcwaork crafts business productivity. This activity aims to provide the skills in pakacging and marketing techniques for crafters and craft of patchwork business owners. The methods were applied to devotion of lectures, demonstration and exercise. The resullt in this community service activity, showed an increase in the skills of participants in making pakacging and marketing techniques. Suggestion can be submitted include: (1) For business owner in Semarang district, should take the advantage of human resources that have been trained to increase the productivity. (2) It takes longer to train the new participant to be able do the marketing and pakacging well. (3) It remains to be developed craft of vrious designs by using fabric wastes as row material, in order to obtain the creavity and innovative crafts. (4) For organizations devoted to the community (LP2M), training should be followed up with the other skill, such as: knitting, embroydery, accessories, etc. (5) Needs the net work with other department, such as Department of Industri in Semarang District, Chamber of Commerrse of Central Java andd others.